2015
DOI: 10.1093/hmg/ddv463
|View full text |Cite
|
Sign up to set email alerts
|

A polygenic burden of rare variants across extracellular matrix genes among individuals with adolescent idiopathic scoliosis

Abstract: Adolescent idiopathic scoliosis (AIS) is a complex inherited spinal deformity whose etiology has been elusive. While common genetic variants are associated with AIS, they explain only a small portion of disease risk. To explore the role of rare variants in AIS susceptibility, exome sequence data of 391 severe AIS cases and 843 controls of European ancestry were analyzed using a pathway burden analysis in which variants are first collapsed at the gene level then by Gene Ontology terms. Novel non-synonymous/spli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 28 publications
5
54
0
Order By: Relevance
“…For a long time, it was believed that the inheritance was a result of autosomal dominant [222324] and because of a lack of male to female transmissions [25]. In our study, we found a similarity between patients and fathers rather than between patients and mothers at the genetic level.…”
Section: Discussionsupporting
confidence: 47%
“…For a long time, it was believed that the inheritance was a result of autosomal dominant [222324] and because of a lack of male to female transmissions [25]. In our study, we found a similarity between patients and fathers rather than between patients and mothers at the genetic level.…”
Section: Discussionsupporting
confidence: 47%
“…Two other common variants of interest have recently been found to be associated with IS, but have yet to be replicated (Table 2) [63, 68]. New methodologies such as exome-sequencing have made it possible to identify rare variants associated with idiopathic scoliosis [4749, 81]. The importance of these findings in the general idiopathic scoliosis population, however, remains to be seen.…”
Section: Resultsmentioning
confidence: 99%
“…Haller et al [49] exome-sequenced 391 severe adolescent IS cases and 843 controls. Using a pathway burden analysis, they found that variants in extracellular matrix genes, especially in musculoskeletal collagen, were significantly enriched in adolescent IS cases compared to controls.…”
Section: Summary Of Genetic Findings In Idiopathic Scoliosismentioning
confidence: 99%
“…Ostensibly, it extends a simplistic paradigm in which damaging mutations with large effects cause Mendelian disorders whereas less damaging coding variants (e.g., hypomorphic or inhibitory) or regulatory polymorphisms confer risk of common forms of the same disorder. 45,46 However, it is clear that the relationship between genotype and phenotype at the GRHL3 locus is not so simplistic. In our previous work, we demonstrated that dominant GRHL3 mutations cause VWS.…”
Section: Discussionmentioning
confidence: 99%